New Retinal Pigment Epithelial Cell Model to Unravel Neuroprotection Sensors of Neurodegeneration in Retinal Disease - Asatryan, Aram; Calandria, Jorgelina M.; Kautzmann, Marie-Audrey I.; Jun, Bokkyoo; Gordon, William C.; Do, Khanh V.; Bhattacharjee, Surjyadipta; Pham, Thang L.; Bermúdez, Vicente; Mateos, Melina Valeria; Heap, Jessica; Bazan, Nicolas G. (Frontiers in Neuroscience, 2022)
Retinal pigment epithelial (RPE) cells sustain photoreceptor integrity, and when this function is disrupted, retinal degenerations ensue. Herein, we characterize a new cell line from human RPE that we termed ABC. These cells remarkably recapitulate human eye native cells. Distinctive from other epithelia, RPE cells originate from the neural crest and follow a neural development but are terminally differentiated into “epithelial” type, thus sharing characteristics with their neuronal lineages counterparts. Additionally, they form microvilli, tight junctions, and honeycomb packing and express distinctive markers. In these cells, outer segment phagocytosis, phagolysosome fate, phospholipid metabolism, and lipid mediator release can be studied. ABC cells display higher resistance to oxidative stress and are protected from senescence through mTOR inhibition, making them more stable in culture. The cells are responsive to Neuroprotectin D1 (NPD1), which downregulates inflammasomes and upregulates antioxidant and anti-inflammatory genes. ABC gene expression profile displays close proximity to native RPE lineage, making them a reliable cell system to unravel signaling in uncompensated oxidative stress (UOS) and retinal degenerative disease to define neuroprotection sites.